Improvement of illumination in architectural studio workplace through fenestration study / Emir Adam Zaidi and Fazidah Hanim Husain - Zaidi, Emir Adam; Husain, Fazidah Hanim (2018)
In relation to the human productivity of work, illuminance does play a big role. Daylight is the most reliable source of lighting than artificial lighting because it gives more pleasant environment inside the spaces. Thus, daylight is the main source of lighting chosen. It can gives student a better working environment visually. To provide an effective internal illumination, arrangements of the openings with proper type of opening is important. This research focused on the numerous types and materials of the fenestrations, in order to identify the quantity and quality of daylight that enter the residential buildings.